Analysis of the stability of the banking sector by assessing the quality of liquidity management - Grigoreva, Yana I. (Journal of the Belarusian State University. Economics, 2021)
The increased demand for foreign currency in the domestic currency market in August 2020, as well as a significant outflow of resources from Bank accounts during this period, formed serious prerequisites for the deterioration of banks. The assessment of financial stability of Belarusian banks in the conditions of ruble liquidity shortage, as well as the analysis of financial institutions’ compliance with the liquidity standards set by the National Bank of the Republic of Belarus are devoted.